DAMPAK LINGKUNGAN HIDUP AKIBAT PERTAMBANGAN PASIR ILEGAL DI INDONESIA - Siratni, Mia (Ensiklopedia of Journal, 2024)
Mining activities carried out in Indonesia initially did not have too big an impact, but because this was carried out continuously for too long, over time it caused a big impact. This happens because the activity itself is carried out continuously on an increasing scale every day. The mining carried out also uses modern tools, so that it can increase the amount of sand exploitation. According to the author, ways to deal with illegal sand in Indonesia are: 1) The government must immediately regulate illegal sand mining activities in accordance with applicable regional regulations; 2) Providing education to the community regarding good and correct sand mining activities so that they do not damage the natural environment and so that land resources remain available. Apart from that, outreach to jointly protect the surrounding environment so that natural resources remain stable; 3) The government must make efforts to open up employment opportunities so that once these sand miners are disciplined, they are not unemployed; 4) Restrictions on granting sand mining permits; 5) Limitation on population; and 7) Residents must take sand gradually, not immediately on a large scale.Keywords: Environment, Mining, Sand, Illegal